Tissue-Type Plasminogen Activator in Patients with Intracranial Meningiomas - Tsuda, Hiroko; Oka, Kazunari; Noutsuka, Youko; Sueishi, Katsuo (Thrombosis and Haemostasis, 1988)
Three of 13 patients with intracranial meningiomas showed the pre- and postoperative elevation of tissue-type plasminogen activator (t-PA) related fibrinolytic activity in euglobulin fractions (EFA). During operation, two of these three patients showed a significant elevation of the level of fibrin(ogen) degradation products and oozing in the operating field. However, oozing was not observed in the third patient who had been given tranexamic acid preoperatively. Fibrin autography revealed that a broad lytic band of mol wt 50–60 kDa, probably free t-PA, appeared in the plasma obtained from two of the three patients after operation when EFA elevated significantly. In all patients studied, the t-PA antigen levels were normal preoperatively but increased both during and after operation, and correlated mainly with the intensities of a lytic band of mol wt 110 kDa, probably t-PA complexed with its major inhibitor (PAI–1). These results suggest that the excessive fibrinolysis can induce the local hemorrhagic diathesis during operation and may be related to t-PA function in plasma
Keywords: Intracranial meningiomas; Euglobulin fibrinolytic activity; Tissue-type plasminogen activator